Activation of NRF2 blocks HIV replication and apoptosis in macrophages. Issue 1 (January 2023) - Han, Dating; Lu, Xiangyun; Yin, Wanpeng; Fu, Haijing; Zhang, Xiaodi; Cheng, Linfang; Liu, Fuming; Jin, Changzhong; Tian, Xuebin; Xie, Yiwen; Wu, Nanping
Abstract: Abnormal oxidative stress caused by human immunodeficiency virus (HIV) infection affects viral replication and causes non-acquired immune deficiency syndrome-related complications in infected individuals. The transcription factor NFE2-related factor 2 (NRF2), a key regulator of oxidative stress, responds to abnormal oxidative stress by regulating the expression of NRF2-dependent cytoprotective genes. The present study aimed to determine whether inhibition of oxidative stress could control HIV replication and improve cell survival. In this study, the NRF2 activator, methyl bardoxolone, was used to treat cells for HIV infection. The effects on HIV replication and apoptosis pathways were confirmed by NRF2 activation or knockdown . The results showed that NRF2 activation could block HIV replication in macrophages before the integration phase and inhibited the expression of apoptotic pathways in virus-exposed macrophages. The study presents an unconventional anti-viral strategy of activation antioxidant response for HIV infection blocking. Abstract : HIV; Oxidative stress; Inflammation; Macrophage; Apoptosis